(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Radiological diagnostic methods play a crucial role in every stage of managing patients with brain tumors. From the initial diagnosis to treatment planning and monitoring the effectiveness of therapy, accurate and detailed imaging is essential for optimal care. By leveraging advanced imaging techniques like magnetic resonance imaging (MRI), clinicians can precisely identify the location, size, and characteristics of brain tumors without invasive procedures. This information is invaluable for developing personalized treatment plans and assessing the response to therapy over time. MRI has indeed become a cornerstone of contemporary neurovisualization methods due to its unparalleled capabilities in assessing structural transformations in the brain and exploring various features of tumors. Despite the emergence of novel methodologies, traditional structural MRI remains indispensable in neuro- oncology practice due to its high resolution and the reliability of its results. The field of neuroradiology continues to advance, with ongoing efforts focused on the development of new scanning protocols, enhancement of image quality, and integration of functional MRI methods. These advancements aim to provide clinicians with more detailed and accurate information for treatment planning and outcome evaluation, ultimately improving patient care in neuro-oncology